The Eucalyptus Tonoplast Intrinsic Protein (TIP) Gene Subfamily: Genomic Organization, Structural Features, and Expression Profiles - Rodrigues, Marcela I.; Takeda, Agnes A. S.; Bravo, Juliana P.; Maia, Ivan G. (Frontiers in Plant Science, 2016)
Plant aquaporins are water channels implicated in various physiological processes, including growth, development and adaptation to stress. In this study, the Tonoplast Intrinsic Protein (TIP) gene subfamily of Eucalyptus, an economically important woody species, was investigated and characterized. A genome-wide survey of the Eucalyptus grandis genome revealed the presence of eleven putative TIP genes (referred as EgTIP), which were individually assigned by phylogeny to each of the classical TIP1–5 groups. Homology modeling confirmed the presence of the two highly conserved NPA (Asn-Pro-Ala) motifs in the identified EgTIPs. Residue variations in the corresponding selectivity filters, that might reflect differences in EgTIP substrate specificity, were observed. All EgTIP genes, except EgTIP5.1, were transcribed and the majority of them showed organ/tissue-enriched expression. Inspection of the EgTIP promoters revealed the presence of common cis-regulatory elements implicated in abiotic stress and hormone responses pointing to an involvement of the identified genes in abiotic stress responses. In line with these observations, additional gene expression profiling demonstrated increased expression under polyethylene glycol-imposed osmotic stress. Overall, the results obtained suggest that these novel EgTIPs might be functionally implicated in eucalyptus adaptation to stress.